1996
DOI: 10.1042/bj3160201
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Ser16 and Thr17 phosphorylation of phospholamban into Ca2+-pump stimulation

Abstract: Stimulation of cardiac sarcoplasmic reticulum Ca 2+-pump activity is achieved by phosphorylation of the oligomeric protein phospholamban at either Ser16 or Thr17. The altered mobility of phosphorylated forms of pentameric phospholamban has been utilized to demonstrate that the mechanisms of phosphorylation of the two sites differ. Phosphorylation of Ser16 by the AMP-dependent protein kinase proceeds via a random mechanism [Li, Wang and Colyer (1990) Biochemistry 29, 4535-4540], whereas phosphorylation of Thr17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…Each phosphorylation is associated with stimulation of the apparent affinity of SERCA2 for Ca 2ϩ . In vivo studies have shown that only Ser 16 and Thr 17 are phosphorylated in cardiac myocytes or perfused hearts (11,12), whereas phosphorylation of PLB by protein kinase C has not been detected in vivo. Phosphorylation of PLB by PKA and CaMKII occurs during ␤-agonist exposure, although the relative contribution of each phosphorylation to the cardiac stimulatory effects is not presently clear.…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
See 2 more Smart Citations
“…Each phosphorylation is associated with stimulation of the apparent affinity of SERCA2 for Ca 2ϩ . In vivo studies have shown that only Ser 16 and Thr 17 are phosphorylated in cardiac myocytes or perfused hearts (11,12), whereas phosphorylation of PLB by protein kinase C has not been detected in vivo. Phosphorylation of PLB by PKA and CaMKII occurs during ␤-agonist exposure, although the relative contribution of each phosphorylation to the cardiac stimulatory effects is not presently clear.…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
“…In vitro studies have shown that PLB can be phosphorylated on Ser 10 by protein kinase C, Ser 16 by cAMP-dependent protein kinase (PKA), and Thr 17 by Ca 2ϩ -calmodulin-dependent protein kinase (CaMKII) (1,9,10). Each phosphorylation is associated with stimulation of the apparent affinity of SERCA2 for Ca 2ϩ .…”
Section: Phospholamban (Plb)mentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Phosphorylation site-specific PLB antibodies 27 were used in the present study to determine whether ␤-AR subtype stimulation differentially regulates PLB phosphorylation. In the absence of ␤-AR stimulation, only a minor PLB phosphorylation is detectable.…”
Section: Plb Phosphorylationmentioning
confidence: 99%
“…Phosphorylation of phospholamban on one of a number of sites (Ser-16, cAMP-dependent protein kinase; Thr-17, CaMKII; Ref. 19) abrogates the inhibitory influence of phospholamban (20), to reveal enhanced Ca 2ϩ transport activity at all physiological Ca 2ϩ concentrations. The kinetic basis of inhibition and subsequent activation of Ca 2ϩ transport is complex; involving contributions from the acceleration of particular reaction steps in the catalytic cycle of SERCA (21) and an increase in the coupling efficiency between ATP hydrolysis and Ca 2ϩ movement (13).…”
mentioning
confidence: 99%